2022
DOI: 10.3390/ijerph191710492
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Low Back Pain Risk among Rubber Harvesters

Abstract: Low back pain (LBP) is a significant work-related musculoskeletal disorder among rubber farmers. This major occupational health problem was highly reported in the agricultural sector. While rubber farming is a profession with high risk of LBP, predictors for LBP remain unclear. This study was designed to investigate the risk predictors of LBP among rubber farmers during the harvesting process. A cross-sectional study was conducted between January and March 2021, in which an interviewer administered a pretested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The values of the variables included in the equation can be found in Table 3. Manual work, heavy lifting, and frequency of loads handling have been associated with LBP among farmers (10). In the present study, a survey conducted among CPs in Chinchiná and Palestina revealed a high point prevalence of LBP, reaching 58.2% (95% CI 48-68).…”
Section: Resultsmentioning
confidence: 46%
See 2 more Smart Citations
“…The values of the variables included in the equation can be found in Table 3. Manual work, heavy lifting, and frequency of loads handling have been associated with LBP among farmers (10). In the present study, a survey conducted among CPs in Chinchiná and Palestina revealed a high point prevalence of LBP, reaching 58.2% (95% CI 48-68).…”
Section: Resultsmentioning
confidence: 46%
“…However, Barrero (31) reported higher LBP prevalence among a rural rice farmers in China, with a one-year prevalence of 64% (CI 63.1-65.0) and the highest prevalence (61%) observed in male subjects aged 45 and 55. Similarly, rubber harvesters, in Thailand, showed a prevalence of 711.2% (95% CI 0.716-1.900) (10).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Work related MSDs in agriculture or dairy farming are occur due to bending, squatting, kneeling in awkward postures and continuous load lifting for prolonged duration. To reduce the risk of WMSDs, systematic quantification and analysis of risk factors are necessary 15) . Depending on the task or activities perfromed in dairy famring the level of risk and MSDs vary similar to that being observed by author in case of mechanized wood loading.…”
Section: Discussionmentioning
confidence: 99%